Epidemiological Patterns of Animal bite in the North of Khorasan Province in Iran - Mohadeseh Lakzaei; Fatemeh Jafari; Mohammad Mohammadi Abnavi; Saeed Keshvari; Hamed Karami (Journal of Health Sciences and Surveillance System)
Background: Rabies is one of the important diseases and is usually transmitted by the bite of infected animals. This study investigated the epidemiological situation of animal bites in northeastern Iran from 2017 to 2021.Methods: This is a cross-sectional study. Sampling was done by census, and all animal bite cases, including 3679 people, were enrolled in the study. Cases of animal bites registered at the rabies treatment centers by Esfarayen County in the North of Khorasan province, from 2017 to 2021, were analyzed. Thetool for collecting information was the portal of the Ministry of Health, and SPSS version 26.0 was used for data analysis.Results: The mean age of the subjects under study was 33.9±20.4 years; of them, 2636 (71.6) were men and 838 (22.8) were students. 1448 (97.6%) of those with upper body injuries referred to the health center for less than 48 hours. 2024 (94.3%) were bitten by a dog and most of the bites (N=1055, 28.7%) happened in spring. The incidence of animal bites was 25.54 per thousand people. The trend has increased since the beginning of the study from 476 per 100,000 in 2017 to 648 per 100,000 in 2021 (P<0.001).Conclusion: Considering the increase in animal bite cases in Esfarayen County and the loss of life and money caused by it, including the risk of rabies transmission and increasing costs of vaccination and serum therapy, the cooperation of related organizations and interventions is necessary to reduce animal bite cases.